Mycobacterium chelonei Infection: Successful Treatment Based on a Radiometric Susceptibility Test - Arroyo, Julio (1977)
A patient with Mycobacterium chelonei infection was treated with erythromycin stearate and streptomycin. The choice of antibiotics was based on a rapid radiometric susceptibility test developed in our laboratory.